Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
previousshortDOI: 10/ghgng4 previousDOI: 10.5281/zenodo.3885806 EdTechHub.Source: 2405685:CMS6HPI8 EdTechHub.Source: <this> shortDOI: 10/ghgng4 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3875138 10.5281/zenodo.3885806 10.53832/edtechhub.0042 10/ghgng4 2129771:FCNVWJUI 2129771:VJXKA7AN 2339240:FEGWVFS3 2339240:FJ5LQ7QK 2405685:79LULMUU 2405685:BTWBKYN7 2405685:CMS6HPI8 2405685:HLCYI98H 2405685:RV5RNCII
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
ZenodoArchiveID: 4737460 previousDOI: 10.5281/zenodo.4556939 PreviousDOI: 10.5281/zenodo.3958002 PreviousDOI: 10.5281/zenodo.4477168 PreviousShortDOI: 10/ghgnfc Publisher: Zenodo Version Number: 1 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3958002 10.5281/zenodo.3958002 10.5281/zenodo.4477168 10.5281/zenodo.4556939 10.5281/zenodo.4737460 2259720:36F6CWBU 2339240:23GW5XQ8 2339240:6YJ555Q6 2339240:9CAC5BI5 2339240:ABKFKG4Q 2339240:FC5RCEYW 2339240:GCYWZ39Q 2339240:GZYWFIHI 2339240:JMFNCMP8 2339240:L326GM9E 2339240:MQ8QSK5B 2339240:PB295ID7 2339240:Q8QJYXRQ 2339240:TIVTGHAA 2339240:TYYDMDPR 2339240:VFBZXUEM 2339240:VFBZXUEM; 2339240:WVUDHTHF 2405685:4XTHDWDA 2405685:6PE7ANUL 2405685:78VECZYK 2405685:ALEXQL2P 2405685:BLT5KKXG 2405685:C4JLZV3D 2405685:CZBRW85R 2405685:E4TFYPYP 2405685:IV7MEXRW 2405685:NMXFFTIB 2405685:PKS7U5LC 2405685:RTIHY6H8 2405685:S5PCWMRP 2405685:SA26Q7UG 2405685:V7VESTKX 2405685:WR37F768 2405685:YHERHZKV 2405685:YNMUHK9S 2534378:5794CXFP 2534378:5GTJL9K7 4804264:EZB37W4S
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode